2009
DOI: 10.1098/rstb.2009.0090
|View full text |Cite
|
Sign up to set email alerts
|

Developmental basis of the rostro-caudal organization of the brainstem respiratory rhythm generator

Abstract: The Hox genetic network plays a key role in the anteroposterior patterning of the rhombencephalon at pre-and early-segmental stages of development of the neural tube. In the mouse, it controls development of the entire brainstem respiratory neuronal network, including the pons, the parafacial respiratory group (pFRG) and the pre-Bö tzinger complex (preBö tC). Inactivation of Krox20/Egr2 eliminates the pFRG activity, thereby causing life-threatening neonatal apnoeas alternating with respiration at low frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…In contrast, other investigators have proposed that pFRG activity represents an expiratory oscillator that interacts with the inspiratory oscillator in the pre-BötC to generate coordinated patterns of inspiratory and expiratory activity (Feldman & Del Negro 2006;Janczewski & Feldman 2006, also see the following). Thus, an emerging view is that the RTN/pFRG compartment may contain functionally distinct populations of neurons involved in several interrelated basic functions, including coordinating inspiratory and expiratory activities in a metabolic statedependent manner (see Champagnat et al 2009 for additional information on structural/functional organization, including developmental origins).…”
Section: Spatially Arrayed Functional Respiratory Compartments: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other investigators have proposed that pFRG activity represents an expiratory oscillator that interacts with the inspiratory oscillator in the pre-BötC to generate coordinated patterns of inspiratory and expiratory activity (Feldman & Del Negro 2006;Janczewski & Feldman 2006, also see the following). Thus, an emerging view is that the RTN/pFRG compartment may contain functionally distinct populations of neurons involved in several interrelated basic functions, including coordinating inspiratory and expiratory activities in a metabolic statedependent manner (see Champagnat et al 2009 for additional information on structural/functional organization, including developmental origins).…”
Section: Spatially Arrayed Functional Respiratory Compartments: Overviewmentioning
confidence: 99%
“…It has been suggested that a neural oscillator in the pFRG interacts with the pre-Bö tC inspiratory oscillator to generate coordinated patterns of inspiratory and expiratory activity in neonatal rodents. While there is currently no clear consensus about the nature and functional role of this mechanism, there has been intense general interest in properties of the pFRG, including developmental origins (Champagnat et al 2009). This has been bolstered by data of Guyenet et al (2005), who have shown that the RTN, which as noted earlier spatially overlaps the pFRG, appears to provide a fundamental chemosensory drive to the VRC.…”
Section: Other Oscillatory Mechanisms In the Networkmentioning
confidence: 99%
“…Its absence results in the loss of neurons in the retrofacial nucleus, a key region mediating central chemosensitivity. Moreover, neurons in this region in the embryo appear to be autorhythmic at an earlier stage of development, which was suggested as key to the normal development of the central pattern generator for breathing (Champagnat et al 2009). After birth, neurotrophic factors play a major role in the development of neurons, synaptic activity and connectivity at the level of the KollikerFuse nucleus in the pons (Mö rschel & Dutschmann 2009).…”
Section: Problems Tackled By Papers In This Issue Of Philosophical Trmentioning
confidence: 99%
“…All exemplify and make use of novel techniques and new preparations. Thus, for the first time, it has now become possible to record the activity of large numbers of neurons simultaneously by multi-electrode arrays (Nuding et al 2009) and by optical methods, without electrodes (Champagnat et al 2009;Homma et al 2009;Muller et al 2009;Smith et al 2009). Inevitably, when one records from vast numbers of cells at once, complexities arise in both analysis and interpretation that require sophisticated computational programmes (Nuding et al 2009;Smith et al 2009).…”
Section: Problems Tackled By Papers In This Issue Of Philosophical Trmentioning
confidence: 99%
See 1 more Smart Citation